Towards Neuroresponsibility's model: a perspective of social responsibility since human development - Juan José Martí Noguera (Universidad de San Buenaventura, 2011)
The rise of neuroscience's study, based on the technological development that allows to investigate brain processes by neuroimaging, has led to a new research area which after the neuro  prefix covers studies such as neuroeconomics, neuromarketing and social neuroscience . This paper provides a review based on different research projects with the aim of presenting social responsibility, often conceptually linked to organizational paradigms, as an evolutionary trend of neurological human development, which could be called Neuro-responsibility.